Penerapan Model Pembelajaran Berbasis Masalah Untuk Meningkatkan Hasil Belajar Siswa Pada Materi Sifat-Sifat Bilangan Berpangkat di Kelas X 1 MAN 2 Pidie Jaya - Fahmi, Arizal (RISDA : Jurnal Pemikiran dan Pendidikan Islam, 2021)
This study aims to determine the application of problem-based learning models can improve student learning outcomes on the material properties of rank numbers in class X.1 MAN 2 Pidie Jaya. This type of research is Classroom Action Research. Data collection is carried out by planning (planning), action (action), observation (observation), and reflection (reflection). Data analysis was done descriptively. The results of data analysis showed that the acquisition of student learning outcomes with an average value in the first cycle: 60.31, the second cycle: 69.69, and the third cycle: 81.56. Student learning completeness in the first cycle: 18.75%, the second cycle: 56.25%, and the third cycle: 93.75%. Thus, it can be concluded that the application of a problem-based learning model to the material properties of exponents can improve student learning outcomes. This can be seen by the large participation of students during the learning process, as well as the interest of students to share experiences and information with their friends. So that all students can understand each material presented either through the explanation of the researcher or through the guidance and direction of his friends.